Metal-organic framework (MOF)-derived catalysts for fine chemical production - Konnerth, Hannelore; Matsagar, Babasaheb M.; Chen, Season S.; Prechtl, Martin H.G.; Shieh, Fa-Kuen; Wu, Kevin C.-W. (Coordination chemistry reviews, 2020)
•An overview of the fast-developing research field of MOF-derived catalysis is presented.•Design and synthesis of highly active MOF-derived catalysts are introduced.•The relation between the structure of MOF-derived catalysts and their reactivity is well reviewed.•MOF-derived catalysis for oxidation, epoxidation, reduction, cross-coupling reactions are presented. Metal-organic frameworks (MOFs) and MOF-derived materials receive growing attention for fine chemical synthesis due to their versatile tunability and high catalytic activity, further, the MOF-derived materials allow high controllability in the design of catalyst systems for organic reactions. This review provides an overview of this fast-developing research field and presents how catalysts can be designed, and synthesis conditions can be adjusted to obtain highly active MOF-derived catalysts. Although diverse reactions are carried out using MOFs and MOF-derived catalysts such as oxidations and reductions of various functional groups, coupling reactions, acid- and base-catalysis, the understanding of the structure–reactivity relation is a major issue which needs to be addressed for the future development of competent MOF-derived catalysts. Especially in terms of sustainable and energy-efficient processes, catalysts are desired to perform under mild reaction conditions with high selectivity and stability. The chemical composition and the structural properties, such as surface area, porosity, and the dispersion of metal species on the MOF-derived support can be modified according to the desired applications. Thus, MOF-derived materials offer a versatile platform for the synthesis of efficient catalysts in the production of fine chemicals and their intermediates. In this review, an overview of contributions in the progress of the applications of MOF-derived materials in the field of fine chemicals and selected key intermediates, are presented and discussed.